2010
DOI: 10.1016/j.otohns.2010.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optical rhinometry for nasal provocation testing in allergic and nonallergic subjects

Abstract: This initial study demonstrates a correlation between subjective symptoms of nasal patency and objective measurements with the optical rhinometer. Less histamine amount necessary to incite nasal congestion in allergic rhinitis suggests that these patients may be primed to the effects of histamine. These preliminary data suggest that optical rhinometry is able to assess changes in nasal patency during challenges with histamine and oxymetazoline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Optical rhinometry is a relatively new technique, used not only in nasal allergy diagnostics [14] but also as an objective assessment of the effectiveness of treatment and physiological changes in the nasal cavity. There is only one publication documenting the specificity and sensitivity of ORM versus ARM in the literature on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Optical rhinometry is a relatively new technique, used not only in nasal allergy diagnostics [14] but also as an objective assessment of the effectiveness of treatment and physiological changes in the nasal cavity. There is only one publication documenting the specificity and sensitivity of ORM versus ARM in the literature on the subject.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publications from our laboratory have reported that optical rhinometry correlates well with a patient's subjective symptoms in allergic rhinitis . This technique for nasal patency has several advantages to other techniques such as acoustic rhinometry and acoustic rhinomanometry including ability to obtain continuous measurements and minimal user variability, but further work is necessary to prove its utility in the clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Optical rhinometry has shown positive correlation with symptom scores for nasal congestion in nasal provocation testing with histamine and other known antigens. Changes in optical density measured by optical rhinometry also correlate with changes in nasal cavity cross‐sectional area as measured by acoustic rhinometry …”
mentioning
confidence: 87%
“…Some studies support the use of optical rhinometry in allergen provocation challenges. 84,85 Specifically, Luong et al reported that this method can assess changes in nasal patency during challenges with histamine. 85 Also, Krzych-Fałta et al performed optical rhinometry in 30 patients with allergic rhinitis and 30 healthy subjects.…”
Section: Optical Rhinometrymentioning
confidence: 99%
“…84,85 Specifically, Luong et al reported that this method can assess changes in nasal patency during challenges with histamine. 85 Also, Krzych-Fałta et al performed optical rhinometry in 30 patients with allergic rhinitis and 30 healthy subjects. They reported that the level of light extinction in patients with allergic rhinitis returned to baseline after 28.15 minutes.…”
Section: Optical Rhinometrymentioning
confidence: 99%